2013
DOI: 10.1152/japplphysiol.00979.2013
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic response to passive movement and active exercise in individuals with peripheral arterial disease

Abstract: Peripheral arterial disease (PAD) is caused by atherosclerosis and is associated with microcirculatory impairments in skeletal muscle. The present study evaluated the angiogenic response to exercise and passive movement in skeletal muscle of PAD patients compared with healthy control subjects. Twenty-one PAD patients and 17 aged control subjects were randomly assigned to either a passive movement or an active exercise study. Interstitial fluid microdialysate and tissue samples were obtained from the thigh skel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 54 publications
2
65
0
Order By: Relevance
“…This finding concurs with our previous work showing that eNOS mRNA expression and protein content is similar between PAD patients and healthy older adults [34], suggesting that the capacity for NO production is similar and that removal of NO by ROS is likely responsible for group differences in NO availability. Indeed, PAD patients displayed significantly elevated amounts of muscle NADPH oxidase compared with healthy controls.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 93%
“…This finding concurs with our previous work showing that eNOS mRNA expression and protein content is similar between PAD patients and healthy older adults [34], suggesting that the capacity for NO production is similar and that removal of NO by ROS is likely responsible for group differences in NO availability. Indeed, PAD patients displayed significantly elevated amounts of muscle NADPH oxidase compared with healthy controls.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 93%
“…Previous findings of reduced muscle vascular endothelial growth factor protein content (26) and elevated thrombospondin-1 in the muscle (16) and muscle extracellular fluid (26) also provides some indication that the angiogenic potential of PAD-affected muscle may be impaired. However, the capillary-to-fiber ratio differed only nonsignificantly between the two groups, which is in contrast to other studies (16,45).…”
Section: Discussionmentioning
confidence: 89%
“…On a separate day, VL biopsies were taken from the 14 IC patients and the 10 control participants by a medical practitioner using a Bergstroem needle with suction (26,51). All biopsies were taken from the participants at rest within a 6-wk period.…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies (18, 25), we have shown that in populations with lower levels of muscle VEGF compared with young healthy individuals, the increase in muscle interstitial VEGF levels during exercise are lower. Moreover, in these subjects, training increased both muscle VEGF protein levels and the magnitude of increase in interstitial VEGF with exercise (18,25). It is, however, unclear whether these findings reflect a direct relationship.…”
Section: Capillary-to-fiber Ratio and Vegfmentioning
confidence: 81%
“…Moreover, basal muscle interstitial levels of TSP-1 in healthy humans have also been reported to be unaltered after 4 wk of moderate intensity exercise training (23). In peripheral arterial disease patients, basal levels of muscle interstitial TSP-1 protein have been reported to be elevated, most likely reflecting capillary regression (25). This is the first evaluation of how resveratrol affects interstitial TSP-1 in skeletal muscle.…”
Section: Muscle Timp-1 and Tsp-1 Levelsmentioning
confidence: 84%